Studi Dan Analisa Faktor-faktor Yang Mempengaruhi Kepuasan Pelanggan Pada Sistem Informasi Penjualan Online (e-Commerce) Pada CV Selaras Batik - Himawan Wijaya; Omar Pahlevi; Harriansyah Harriansyah (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2019)
Online or e-commerce businesses in Indonesia continue to seek ideas and innovations to increase the number of customers and also retain old customers, so that it is expected to increase the volume of sales transactions and ultimately provide benefits for e-commerce companies. Research conducted by researchers is a continuation of research from previous research conducted in 2014, where research conducted on this occasion is one form of evaluation of services that have been carried out by CV. Selaras Batik to its customers, so as to provide data and information on satisfaction customers who have made a purchase transaction. Where in this study customer satisfaction factors that will be the focus of the study will be divided into 4 categories which is product factors, price factors, delivery time speed factors and also after sales service factors. Where the four factors are considered factors that can affect customer satisfaction to continue to make transactions in CV. Selaras Batik. The research method that will be used in this research is a combination of sampling data and descriptive analysis, so that this research can produce feedback from customers of CV. Selaras Batik and also can be an optimal marketing strategy for CV. Selaras Batik management to continue to exist amid world competition ecommerce is increasingly stringent and competitive.